Design of Differentiated Learning Model Integrated with Local Wisdom Value to Improve Students' Understanding of Pancasila Profile - Sukirno Sukirno; Makhroji Makhroji; Rizky Nafida (Jurnal Penelitian Pendidikan IPA, 2025)
This study aims for designing learning models integrated differentiated​ with values wisdom local to improve understanding participant educate to Profile Pancasila Students. Background study This based on the importance present capable learning​ accommodate need Study individual at a time to plant values culture local in harmony with dimensions Profile Pancasila students, such as cooperation, independence, reasoning critical, creative, global diversity, and faithful and pious to God Almighty. Study This uses approach research and development (R&D) with the 4D development model (Define, Design, Develop, Disseminate). Subject study consists of from participant educate level education middle in areas that have riches culture strong local. Research results show that the learning model developed effectively in increase understanding participant educate to values in Profile Pancasila Students. This is proven with improvements with average score of pretest value of 63.7% to mark posttest by 83.6%. Integration of wisdom local in the learning process is also proven strengthen involvement students and improve relevance learning with life everyday. Findings This recommend application of learning models differentiate based on wisdom local as alternative innovative in education character in school